Renal infarct in a COVID‐19–positive kidney–pancreas transplant recipient. Issue 11 (24th June 2020) - Xu, Jieqing J.; Samaha, Daniel; Mondhe, Suhas; Massicotte‐Azarniouch, David; Knoll, Gregory; Ruzicka, Marcel
Abstract : The novel coronavirus disease 2019 (COVID‐19) is associated with increased risk of thromboembolic events, but the extent and duration of this hypercoagulable state remain unknown. We describe the first case report of renal allograft infarction in a 46‐year‐old kidney–pancreas transplant recipient with no prior history of thromboembolism, who presented 26 days after diagnosis of COVID‐19. At the time of renal infarct, he was COVID‐19 symptom free and repeat test for SARS‐CoV‐2 was negative. This case report suggests that a hypercoagulable state may persist even after resolution of COVID‐19. Further studies are required to determine thromboprophylaxis indications and duration in solid organ transplant recipients with COVID‐19. Abstract : A kidney–pancreas transplant recipient with moderate to severe COVID‐19 complicated by late segmental infarction of the kidney allograft highlights a possible association with large‐vessel arterial thrombosis.